2020
DOI: 10.1016/j.ajpc.2020.100106
|View full text |Cite|
|
Sign up to set email alerts
|

Top 10 dietary strategies for atherosclerotic cardiovascular risk reduction

Abstract: Poor dietary quality has surpassed all other mortality risk factors, accounting for 11 million deaths and half of CVD deaths globally. Implementation of current nutrition recommendations from the American Heart Association (AHA), American College of Cardiology (ACC) and the National Lipid Association (NLA) can markedly benefit the primary and secondary prevention of atherosclerotic cardiovascular disease (ASCVD). These include: 1) incorporate nutrition screening into medical visits; 2) refer patients to a regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 84 publications
(386 reference statements)
1
36
0
1
Order By: Relevance
“…It lowers LDL-C and glucose levels and, therefore, has a protective effect against CVD. [136] Lowering of cholesterol is achieved by the binding of fibre to bile acids, thereby escalating its excretion. This inhibits the production of cholesterol by the liver, resulting in lower blood cholesterol.…”
Section: Dietary Fibrementioning
confidence: 99%
See 3 more Smart Citations
“…It lowers LDL-C and glucose levels and, therefore, has a protective effect against CVD. [136] Lowering of cholesterol is achieved by the binding of fibre to bile acids, thereby escalating its excretion. This inhibits the production of cholesterol by the liver, resulting in lower blood cholesterol.…”
Section: Dietary Fibrementioning
confidence: 99%
“…Saturated fatty acids (SFAs) and trans fatty acids (TFAs) have the greatest adverse effect on atherogenic cholesterol levels and are both associated with risk of CVD. [136,141] Increased SFA intakes increase LDL-C levels. [142] TFAs have a HDL-C lowering effect and also increase LDL-C levels and, therefore, increase the risk of CVD.…”
Section: Dietary Fats and Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard flaxseed varieties contain up to 55% alpha-linolenic acid (ALA), representing the richest plant source of omega-3 acids. ALA is considered one of the main cholesterol-lowering and anti-atherosclerotic ingredients [ 10 ] and was shown to suppress the production of proinflammatory interleukins and lower C-reactive protein and serum amyloid-A concentrations in human patients and experimental animals [ 11 ]. However, in contrast to those previous research, current studies found that ALA exhibited very low anti-inflammatory properties, although they could be more pronounced due to its metabolic conversion to very long-chain PUFAs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%